2019
DOI: 10.1002/lt.25467
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Liver Transplant Candidates Toward Organs From Increased‐Risk Donors

Abstract: Increased‐risk donor (IRD) organs make up a significant proportion of the deceased organ donor pool but may be declined by patients on the waiting list for various reasons. We conducted a survey of patients awaiting a liver transplant to determine the factors leading to the acceptance of an IRD organ as well as what strategies could increase the rate of acceptance. Adult liver transplant candidates who were outpatients completed a survey of 51 questions on a 5‐point Likert scale with categories related to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(42 reference statements)
0
16
0
Order By: Relevance
“… 14 , 16 , 24 , 41 A study of liver transplant candidates revealed that variations may occur also based on transplant candidates’ demographics, opinions on donor’s high-risk behaviors, and information received by healthcare professionals. 43 A study on kidney transplant candidates found a significant association of multiple factors including longer waiting time for transplant, lower donor age, inferior donor HIV risk, potential recipient being on dialysis treatment, or being of an older age with a higher chance to consider the NSRD option. However, the study revealed that patients have an equal likelihood of accepting an NSRD kidney from a younger donor as from an older donor with an inferior chance of having HIV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 , 16 , 24 , 41 A study of liver transplant candidates revealed that variations may occur also based on transplant candidates’ demographics, opinions on donor’s high-risk behaviors, and information received by healthcare professionals. 43 A study on kidney transplant candidates found a significant association of multiple factors including longer waiting time for transplant, lower donor age, inferior donor HIV risk, potential recipient being on dialysis treatment, or being of an older age with a higher chance to consider the NSRD option. However, the study revealed that patients have an equal likelihood of accepting an NSRD kidney from a younger donor as from an older donor with an inferior chance of having HIV.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is an ethical duty to protect the donor’s right to privacy and to prevent stigmatization of the nonclinical data of NSRDs with the potential to negatively influence the recipient’s understanding. 43 Last, because some transplant candidates may fear the acquisition of personality traits or behaviors of their donors, 55 , 56 clinicians should prevent undesirable psychological reactions in the posttransplant period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Involving patients in this decision‐making process is clearly desirable and is preferred by many patients [88] but not only poses logistic challenges in a time‐ and resource‐limited situation but also assumes a good level of understanding of complex issues made in a challenging situation and a high degree of health literacy and education and understanding of complex medical language. Those with a higher level of education may be more likely to decline an IRD organ [89]. While it is possible for vulnerable patients to delegate the patient advocacy to another, this adds a further degree of complexity [90].…”
Section: Opportunities For Improving Organ Utilizationmentioning
confidence: 99%
“…Other (and much more controversial) approaches would be to hold surgeons more accountable for declining organs or to question those centres with a very low rate of nonfunction. Publishing decline rates is already done by several organizations, usually at a centre‐level, and may support increased organ utilization [89]. It could be argued that a unit that has no early graft failures may be declining too many organs.…”
Section: Opportunities For Improving Organ Utilizationmentioning
confidence: 99%